Biceps Tenodesis Versus Tenotomy in the Treatment of Lesions of the Long Head of the Biceps Tendon in Patients Undergoing Arthroscopic Shoulder Surgery: A Prospective Double-Blinded Randomized Controlled Trial. Issue 6 (May 2020) - MacDonald, Peter; Verhulst, Fleur; McRae, Sheila; Old, Jason; Stranges, Greg; Dubberley, Jamie; Mascarenhas, Randy; Koenig, James; Leiter, Jeff; Nassar, Mark; Lapner, Peter
Background: The biceps tendon is a known source of shoulder pain. Few high-level studies have attempted to determine whether biceps tenotomy or tenodesis is the optimal approach in the treatment of biceps pathology. Most available literature is of lesser scientific quality and shows varying results in the comparison of tenotomy and tenodesis. Purpose: To compare patient-reported and objective clinical results between tenotomy and tenodesis for the treatment of lesions of the long head of the biceps brachii. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Patients aged ≥18 years undergoing arthroscopic surgery with intraoperative confirmation of a lesion of the long head of the biceps tendon were randomized. The primary outcome measure was the American Shoulder and Elbow Surgeons (ASES) score, while secondary outcomes included the Western Ontario Rotator Cuff Index (WORC) score, elbow and shoulder strength, operative time, complications, and the incidence of revision surgery with each procedure. Magnetic resonance imaging was performed at postoperative 1 year to evaluate the integrity of the procedure in the tenodesis group. Results: A total of 114 participants with a mean age of 57.7 years (range, 34 years to 86 years) were randomized to undergo either biceps tenodesis or tenotomy. ASES and WORC scores improved significantly from pre- to postoperative time points, with a mean difference of 32.3% ( P < .001) and 37.3% ( P < .001), respectively, with no difference between groups in either outcome from presurgery to postoperative 24 months. The relative risk of cosmetic deformity in the tenotomy group relative to the tenodesis group at 24 months was 3.5 (95% CI, 1.26-9.70; P = .016), with 4 (10%) occurrences in the tenodesis group and 15 (33%) in the tenotomy group. Pain improved from 3 to 24 months postoperatively ( P < .001) with no difference between groups. Cramping was not different between groups, nor was any improvement in cramping seen over time. There were no differences between groups in elbow flexion strength or supination strength. Follow-up magnetic resonance imaging at postoperative 12 months showed that the tenodesis was intact for all patients. Conclusion: Tenotomy and tenodesis as treatment for lesions of the long head of biceps tendon both result in good subjective outcomes but there is a higher rate of Popeye deformity in the tenotomy group. Registration: NCT01747902 (ClinicalTrials.gov identifier)